Estudo dos processos de redução carbotérmica de compostos de Zn, Cd e Sn assistidos pela co-pirólise de diferentes biomassas para a obtenção de materiais nanoestruturados - Adriana Veloso Maciel (2010)
Different nanostructures of zinc metal were prepared in horizontal tube furnace from a new carbothermal route, wich involved the reduction of ZnO by different non-conventional carbon source such as tar pitch of Eucalyptus sp (biopich), tar oil, cellulose, black liquor, charcoal, glycerine and polyethylene. Operating condictions used were less severe than inconvenctional processes: temperature below 900 °C, in the absence of catalystic and templates and atmospheric pressure. During pyrolysis of cellulose in the presence of ZnO were obtained nanofower Zn and bio-hydrogen, the latter as a result of the catalytic reforming of volatile organic products, which was confirmed by TPR (Temperature Programmed Reduction). Parallel reactions were performed in a termobalance (TG/DTG/DTA) in order to identify the temperature ranges of thermal degradation of carbon sorces and the reduction of ZnO to Zn.The gases evolved during the thermal treatment of cellulose, black liquor, tar pitch of Eucalyptus sp and mixtures cellulose/ZnO, black liquor/ZnO and biopitch/CdO were monitored by TG/FTIR. Reaction mechanisms were proposed for systems containing cellulose, black liquor and CdO.ZnO nanowires were synthesized through the thermal oxidation of metallic zinc nanowires. Metallic compounds and micro-based nanostructured Sn and Cd were obtained by carbothermal reduction using biopitch as carbon source. The morphology of the synthesized products was investigated using scanning electron microscopy (SEM). The composition of the products was determined by EDS analysis andstructured determined by X-ray diffraction.